The Relationship between Iron-Deficiency Anemia (IDA) and the Function of the Immune System - Chegni, Hamid; Shaker Taheri , Maryam (Archives of Advances in Biosciences, 2024)
Context: Iron deficiency anemia is a common types of anemia in the world with harmful effects on various organs of the body without any diagnostic symptoms. This review article aimed to review the observational studies and clinical trials conducted on the effect of iron deficiency anemia on the immune system. Evidence Acquisition: The results mentioned in this review are obtained from relevant studies published from January 1980 to January 2024 and indexed in PubMed, Google Scholar, Ovid and Scopus. The keywords were iron deficiency anemia, innate and adaptive immune system, cellular and humoral immunity. Results: Iron deficiency anemia can affect the killing of phagocytes and the function and proliferation of T and B lymphocytes. Various factors including the number, gender, and age of the studied samples, the host’s immune system, and the severity of iron deficiency anemia can be influential factors in the reported results. Conclusion: Iron is essential in the function of different organs of the body, especially the immune system. Therefore, the regulation of iron metabolism against pathogenic factors is important in preventing or treating the disease. In individuals suffering from iron deficiency anemia, taking iron supplements through diet or by injection can strengthen their immune system and minimize their vulnerability to infectious diseases.